PEMBERDAYAAN KELUARGA BERSAMA ORANG DENGAN GANGGUAN JIWA PASCA PASUNG MELALUI KERAJINAN BAMBU BERBASIS LOCAL WISDOM DAN KOMUNIKASI TERAPEUTIK UNTUK MENUNJANG EKONOMI KELUARGA - Wahyuningsih, Sri; Medhy Aginta Hidayat; Yudho Bawono; Anis Fitriyah; Ahmad In’am Kholifi (Dharma: Jurnal Pengabdian Masyarakat, 2025)
In Madura, especially Sampang district, there have been many successes in releasing ODGJ from confinement in stocks, with 1333 successfully released from detention in stocks. This is very supportive of the Government's program to free people from pasung by 2024. Families who are shackled are on average in a weak economic condition, so they do not want to send their family to a mental hospital. They think that the treatment for ODGJ is expensive. The results of the observations of the Pengabdhi and the Abdimas team, that the condition of the families of People with Mental Disorders (ODGJ) in Sampang Madura is categorized as economically weak, meaning that the family with their family members who are ODGJ after being shackled really need help both material approaches and mental rehabilitation assistance from Pengabdhi and community service team in collaboration with the Bina Insan Madulang Group and the Omben Health Center, Sampang Regency. The method in this service is to provide training by empowering families with ODGJ to make handicrafts from bamboo materials by utilizing the village's potential in the form of bamboo plants. The results of handicrafts from bamboo will provide economic value for the family and ODGJ. ODGJ's mental condition is getting better because indirectly cognitive, affective, and psychomotor gradually recover by experiencing improved mental and reproductive health in the community.